2022
DOI: 10.3390/jcm11237005
|View full text |Cite
|
Sign up to set email alerts
|

Hemoadsorption in Complex Cardiac Surgery—A Single Center Experience

Abstract: (1) Background: Cardiac surgery may evoke a generalized inflammatory response, typically magnified in complex, combined, redo, and emergency procedures with long aortic cross-clamp times. Various treatment options have been introduced to help regain control over post-cardiac surgery hyper-inflammation, including hemoadsorptive immunomodulation with CytoSorb®. (2) Methods: We conducted a single-center retrospective observational study of patients undergoing complex cardiac surgery. Patients intra-operatively tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The search yielded 10 articles reporting on studies that enrolled patients undergoing elective, but complex cardiac surgical procedures (Table 2 ). Eight of the 10 studies were RCTs, six original and two post hoc subgroup analyses from the oldest RCT in this group from Bernardi et al [ 15 ], while the remaining two studies were a prospective case series [ 16 ], and a retrospective comparative study [ 17 ]. The total cohort of this subgroup comprised 109 patients treated with hemoadsorption and 131 controls (subjects from post hoc analyses excluded) in the period 2016–2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded 10 articles reporting on studies that enrolled patients undergoing elective, but complex cardiac surgical procedures (Table 2 ). Eight of the 10 studies were RCTs, six original and two post hoc subgroup analyses from the oldest RCT in this group from Bernardi et al [ 15 ], while the remaining two studies were a prospective case series [ 16 ], and a retrospective comparative study [ 17 ]. The total cohort of this subgroup comprised 109 patients treated with hemoadsorption and 131 controls (subjects from post hoc analyses excluded) in the period 2016–2022.…”
Section: Resultsmentioning
confidence: 99%
“…Procedures included open valve surgery, coronary artery bypass grafting (CABG)—isolated and combined [ 15 , 18 , 19 , 24 ], or various other cardiac surgery operations with prolonged CPB times (> 90 min) [ 16 , 17 , 20 , 21 , 23 ], including one study that enrolled patients who underwent combined aortic root and valve surgery [ 22 ]. Hemoadsorption was used exclusively intraoperatively in all studies, however in one study two adsorbers in parallel connection within the CPB circuit were used [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was significant reduction of the VIS after 48 h of treatment as compared to baseline (20 vs 10, P = 0.009). In a recent, observational study of patients undergoing complex cardiac surgery, Manohar et al showed lower VIS in the HA group (HA: 3.5 vs C: 5.5, P = 0.05) compared to controls [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high-risk nature of this patient, as indicated by the high EuroSCORE, the need for redo aortic surgery, the physiological and inflammatory stresses associated with the cardio-pulmonary bypass, an anticipated prolonged cardiopulmonary bypass duration, and the fact that it was an emergency, made it a suitable case for the use of the CytoSorb adsorber. In this regard, there is a good body of evidence on the beneficial prophylactic use of intraoperative CytoSorb hemoadsorption in patients undergoing invasive high-risk cardiothoracic procedures [ 11 , 20 23 ]. Besides other effects, these studies show an attenuation in the severity of postoperative sepsis [ 20 ], improved lung function and shortened duration of ventilator use411,21], mitigated inflammatory response [24], accelerated recovery of multiorgan and microcirculatory dysfunction [ 22 ], improved hemodynamic stability [ 23 ], and reduced sepsis-associated mortality [ 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%